Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.socnet.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

How MPs ties to interest groups matter for legislative co-sponsorship

Abstract: This article investigates whether linkages between members of parliament (MPs) and interest groups matter for MPs' activities of co-sponsoring legislative proposals. Based on statistical models for network data, the study builds on classical explanations of cosponsorships highlighting the role of similar ties between MPs, such as party membership, legislative committee assignments, electoral district or gender. It shows that, on top of these traditional forms of homophily, MPs' ties to interest groups also mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 50 publications
(52 reference statements)
1
32
0
1
Order By: Relevance
“…We complement this work by investigating cooperation between parliamentarians within and across political parties and between parliamentarians and different types of interest groups. We consider such a broader perspective on parliamentarians’ and parties’ behavior in (EU) policy-making analytically important, since politicians need to cooperate with other political actors to win formal and informal support for the successful formulation and adoption of policies (Fischer et al., 2019; Grossmann, 2014; Grossmann and Dominguez, 2009; Koger et al., 2009; Varone et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We complement this work by investigating cooperation between parliamentarians within and across political parties and between parliamentarians and different types of interest groups. We consider such a broader perspective on parliamentarians’ and parties’ behavior in (EU) policy-making analytically important, since politicians need to cooperate with other political actors to win formal and informal support for the successful formulation and adoption of policies (Fischer et al., 2019; Grossmann, 2014; Grossmann and Dominguez, 2009; Koger et al., 2009; Varone et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Business associations could also not be included in the measure because they arguably provide both types of benefits. Not only are they strong providers of political support (Fischer et al 2019;Grossmann and Dominguez 2009;Wonka and Haunss 2019), anecdotal evidence also emphasises very attractive salaries. 6 The resulting measurement is given as the proportion of the two benefit types, or more specifically as:…”
Section: Dependent and Key Independent Variablesmentioning
confidence: 99%
“…Past research has demonstrated that leadership positions on the boards of IGs help candidates receive significantly more preference votes during elections (Lutz et al ). Once elected, the same IG ties help parliamentarians secure support for their policy proposals (Fischer et al ). Our operationalisation is based on the reasonable assumption that these types of side jobs on average often come with much more moderate financial compensation or are even unpaid.…”
Section: Data and Operationalisationmentioning
confidence: 99%
“…One form of social relation among MPs visible to the public and relatively simple to assess for researchers is the co-sponsorship of parliamentary proposals (Ringe et al 2016). Co-sponsoring parliamentary proposals signals support between MPs and may result from similar policy preferences or strategic considerations (Fischer et al 2019). Co-sponsorship hints at a joint effort by multiple MPs, who may represent a variety of ideological positions (Craig 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Empirically, the legislature gives the impetus to about 30% of legislative processes, whereas the executive initiates about half of the processesthe remainder stem from the people (through popular initiatives) or the international arena (Jaquet 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 274 275 276 277 278 279 280 281 282 283 284 285 286 287 288 289 290 291 292 293 294 295 296 297 298 299 300 Sciarini et al 2002). While MPs submit parliamentary initiatives, motions and postulates in their name, they often look for co-sponsors to demonstrate broad support and increase chances of later acceptance (Fischer et al 2019). Therefore, co-sponsorship is definitely more than 'cheap talk'.…”
Section: The Swiss Parliamentmentioning
confidence: 99%